1992
DOI: 10.1111/j.1095-8649.1992.tb02570.x
|View full text |Cite
|
Sign up to set email alerts
|

Territoriality and microhabitat selection in two intertidal New Zealand fish

Abstract: Aspects of territoriality and microhabitat selection in Acunthoclinus fuscus and Forsferygiun nigripenne rubustum were studied in intra-and interspecific confrontation experiments under tidal and constant conditions. In both species aggressive responses were closely related to activity with maximal frequencies during the first 2 h of the experiments. Under tidal conditions activity was higher than at constant water level. Size predominantly affected contest outcome in both species. Initiation of the first bout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 28 publications
2
34
0
Order By: Relevance
“…Gibson, 1972;Koppel, 1988;Mayr and Berger, 1992), or any other effect of species domination, although it must be recognized that most studies evaluated resilience and were not designed to detect competition. Lack of evidence may reflect insufficient rigor in the investigation to address this question.…”
Section: Factors That May Control Rocky Intertidal Fish Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gibson, 1972;Koppel, 1988;Mayr and Berger, 1992), or any other effect of species domination, although it must be recognized that most studies evaluated resilience and were not designed to detect competition. Lack of evidence may reflect insufficient rigor in the investigation to address this question.…”
Section: Factors That May Control Rocky Intertidal Fish Populationsmentioning
confidence: 99%
“…Itzkowitz, 1977;Brock et al, 1979;Behrents, 1987;Larson, 1980a, b, c;Jones, 1987a, b;Dufour and Galzin, 1992;Mayr and Berger, 1992). The rocky intertidal habitat is a harsh and strongly fluctuating environment, subjected to frequent disturbances (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A.fuscus showed a remarkable tolerance of aerial exposure for up to 5 h (Mayr & Berger 1992). F. n. robustum was rarely found entirely out of water and was poorly represented in the intertidal zone during summer.…”
Section: Kaikouramentioning
confidence: 99%
“…Other studies of rock intertidal fishes that provide evidence that access to shelter is an important resource at stake in agonistic encounters are those of Grossman (1980), Behrents (1987), Koppel (1988), and Mayr and Berger (1992). Faria et al (1998b) partly tested this hypothesis, demonstrating that there is a significant correlation between the dominance rank of each fish in a group and the time spent in shelters.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have reported the presence of agonistic behaviour in adult males of other species as well as in adult females and juveniles (e.g. Phillips 1977;Wirtz 1978;Almada et al 1983Almada et al , 1990Mayr and Berger 1992;Gonçalves et al 1996;Faria et al 1998a). In his successive reviews on the behaviour of littoral fishes, Gibson (1969Gibson ( , 1982Gibson ( , 1986Gibson ( , 1988Gibson ( , 1999 summarised the available information on the subject.…”
Section: Introductionmentioning
confidence: 99%